Panel discussion: emotional symptoms of behavioural disorders & understanding the tried-and-tested ways of managing our women - Mohd Arifin, Siti Roshaidai (2018)
Maternal emotional disorders may include anxiety, worry, postnatal blues, depression and puerperal psychosis. Whilst it is well-known that such disorders could compromise maternal-infant relationships, may affect their ability to participate in normal activities, and interfere with their family and other social relationships, many women were reluctant to disclose their emotional symptoms to healthcare practitioners. The reasons for not revealing their inner turmoil were associated with many factors but were commonly linked with the stigmatisation of a mental health diagnosis, such as concern it would make them ‘feel weak’, fear they would be judged as a ‘bad mother’, have limited understanding of emotional disorders, did not recognise and/or normalised the symptoms, and believed that their distress would get better by adopting self-help measures. It is recommended that healthcare practitioners should have appropriate skills to assess emotional disorders in women attending for antenatal and postnatal healthcare. Nevertheless, studies found that the healthcare practitioners reported that their roles in managing women with emotional disorders were challenged by the social and cultural stigma and this was limiting the women’s willingness to seek help. There is potential to prevent maternal emotional disorders and to educate and support the women through community-based interventions. There were three potential interventions proposed: screening programmes, an education and awareness campaign, and supportive strategies.